TRENDS IN COMPANIES’ DISCLOSURE GOING PUBLIC: ETHICAL PROSPECT - Erni Rusyani; Taufani C. Kurniatun (TRIKONOMIKA, 2021)
Information disclosure in a go-public company is very important as transparency for stakeholders. This research discusses about trends of disclosure of media company which will go public. It is also carried out by using documentation study on the media company prospectus occurred in 2016-2021. Population is the prospectus of 18 media companies listed in Indonesia Stock Exchange. The data was then assessed by 10 students from department of financial management and 10 students from department of accounting, 10 company leaders and 10 investor practitioners. The data was processed by using Weighted Means Score (WMS). The result showed that the aspect of disclosure, cash flow, type of product/program, investment result, risk and business activity are in open category. The disclosure on assets is in the very open category; while the disclosure on important events is in the fairly open category. A media company that will go public, viewed from the ethical prospect (disclosure trend) towards company’s information is in open category which means it has already been open towards information owned by the company.